Silence: A Novel Co-Produced Experience To Build Community Awareness Of Biodiversity Loss - Bellisario, Kristen; Shee, Christie (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2024)
The current sounds of our world are under threat of disappearing. Undergraduate students and interdisciplinary university teams are at the forefront of generating collaborative research opportunities to create community awareness of biodiversity loss and conservation practices. Recent conservation research has focused on how local communities can begin to reverse the trends of biodiversity loss by using private residences and urban spaces. The inclusion of native plants in backyard gardens is an accessible way to promote ecological restoration. In this co-produced instructional exhibit, “Earth Day Celebration: Silence,” we introduce a novel experiential event that connects instructional design with community collaboration. The event was designed to explore the ways in which society can become engaged in the preservation and protection of biodiversity and our sonic world.